Individual heterojunctions of 3D germanium crystals on silicon CMOS for monolithically integrated X‐ray detector (Phys. Status Solidi A 1∕2014). Issue 1 (January 2014) - Kreiliger, Thomas; Falub, Claudiu V.; Taboada, Alfonso G.; Isa, Fabio; Cecchi, Stefano; Kaufmann, Rolf; Niedermann, Philippe; Pezous, Aurélie; Mouaziz, Schahrazède; Dommann, Alex; Isella, Giovanni; von Känel, Hans
<x xml:space="preserve">Abstract</x> Silicon is highly successful in today's electronics, but it provides only very limited potential for new functionalities, such as LED, lasers or radiation detectors. Integrating additional materials directly on the silicon chip would enable those features, but it remains a huge challenge due to material‐related incompatibilities, such as lattice and thermal mismatches. A promising way to solve these issues has recently been presented as 3D heteroepitaxy, where arrays of tall, micrometer sized germanium crystals are grown on deeply patterned silicon substrates. Based on this technique, Kreiliger et al. (pp. 131–135) present a first version of a novel kind of X‐ray detector, where a germanium absorber layer is directly grown on the silicon readout electronics. This approach is expected to improve spatial resolution and sensitivity compared to conventional detectors, while further reducing production costs. As a first proof of concept the authors present dark current measurements on individual Si/Ge heterojunctions, which were performed inside an SEM chamber using a micromanipulator to electrically contact single germanium crystals. The measurements show reverse dark current densities below 1 mA/cm2, which is suitable for detector fabrication. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>